Chemotactic Host-Finding Strategies of Plant Endoparasites and Endophytes - Tsai, Allen Yi-Lun; Oota, Morihiro; Sawa, Shinichiro (Frontiers in Plant Science, 2020)
Plants interact with microorganisms in the environment during all stages of their development and in most of their organs. These interactions can be either beneficial or detrimental for the plant and may be transient or long-term. In extreme cases, microorganisms become endoparastic or endophytic and permanently reside within a plant, while the host plant undergoes developmental reprogramming and produces new tissues or organs as a response to the invasion. Events at the cellular and molecular level following infection have been extensively described, however the mechanisms of how these microorganisms locate their plant hosts via chemotaxis remain largely unknown. In this review, we summarize recent findings concerning the signalling molecules that regulate chemotaxis of endoparasitic/endophytic bacteria, fungi and nematodes. In particular, we will focus on the molecules secreted by plants that are most likely to act as guidance cues for microorganisms. These compounds are found in a wide range of plant species and show a variety of secondary effects. Interestingly, these compounds show different attraction potencies depending on the species of the invading organism, suggesting that cues perceived in the soil may be more complex than anticipated. However, what the cognate receptors are for these attractants, as well as the mechanism of how these attractants influence these organisms, remain important outstanding questions. Host-targeting marks the first step of plant–microorganism interactions, therefore understanding the signalling molecules involved in this step plays a key role in understanding these interactions as a whole.